2014
DOI: 10.1016/j.bbmt.2014.04.027
|View full text |Cite
|
Sign up to set email alerts
|

The Graft-Versus-Myeloma Effect: Chronic Graft-Versus-Host Disease but Not Acute Graft-Versus-Host Disease Prolongs Survival in Patients with Multiple Myeloma Receiving Allogeneic Transplantation

Abstract: We conducted a study of patients with multiple myeloma (MM) undergoing allogeneic transplantation to evaluate outcome parameters. Fifty-seven consecutive patients with MM received an allogeneic transplantation between 2004 and 2011 at our institution. Patients who had received at least 1 prior autologous transplantation were included. Twenty-six patients underwent allogeneic transplantation for consolidation after a response to their first autograft, and 30 patients received an allogeneic transplantation as sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 30 publications
1
36
1
Order By: Relevance
“…In this study, we also aimed to take advantage of the possible protective effect of chronic GvHD on MM relapse. 11,12 Our results challenge the commonly accepted belief that allogeneic HSCT is overly toxic and associated with prohibitive NRM. Despite complete discontinuation of preventive immunosuppression by day +100, we observed a very low incidence of grades II-IV acute GvHD.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…In this study, we also aimed to take advantage of the possible protective effect of chronic GvHD on MM relapse. 11,12 Our results challenge the commonly accepted belief that allogeneic HSCT is overly toxic and associated with prohibitive NRM. Despite complete discontinuation of preventive immunosuppression by day +100, we observed a very low incidence of grades II-IV acute GvHD.…”
Section: Discussioncontrasting
confidence: 45%
“…It is well recognized that grades II-IV acute GvHD is associated with deleterious outcome and lower PFS and OS. 12,18,20,35,39 Conversely, the favorable impact of chronic GvHD on relapse is another important result. We speculate that the higher incidence of chronic GvHD observed in our cohort directly correlates with a GvMM effect and possibly explains the impressive PFS observed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 The prospective BMT CTN 0102 study and a retrospective CIBMTR study also found that the occurrence of cGVHD after allo-SCT correlated with freedom from progressive MM. 33,47 Other single institution studies have also shown that development of cGVHD is significantly associated with better OS, 37,48 further substantiating the GVM effect. Additionally, in vitro or in vivo T-cell depletion has been associated with higher relapse rates and a need for subsequent DLI after allotransplant.…”
Section: Immunomodulationmentioning
confidence: 86%
“…36 In another single institution study, development of cGVHD was associated with favorable OS and PFS further substantiating the importance of GVM effect. 37 Allogeneic transplantation in multiple myeloma B Dhakal et al…”
Section: Non-myeloablative/reduced-intensity Conditioningmentioning
confidence: 99%